Peranan Dinas Kebersihan Dan Pertamanan Peranan Dinas Kebersihan dan Pertamanan Kota Medan dalam Pengelolaan Sampah Rumah Tangga - Nasution, Sahra Yusna; Kadir, Abdul; Batubara, Beby Masitho (Strukturasi: Jurnal Ilmiah Magister Administrasi Publik, 2021)
The purpose of this study is to determine how the Role of the Medan City sanitation and landscaping service in managing household waste in Medan Tembung district in 2019 along with inhibiting factors. The method which is used by researchers is a qualitative research method through observation, interviews, and documentation. The results of the study show the role of the Medan City sanitation and landscaping office in the management of household waste in Medan Tembung district in 2019 measured from four indicators including three indicators can be implemented well including equality,  consensus  orientation,  responsiveness,  and  one of  their  participation  in  the management of household waste was declared less than optimal. Inhibiting factors include inadequate facilities and infrastructure such as garbage rickshaws, cleaning staff, participation, economic factors, and supervision and sanctions/penalties that are still weak for those who litter.